The Interplay Between Dimethyl Sulfide (DMS) and Methane (CH4) in a Coral Reef Ecosystem - Deschaseaux, Elisabeth S. M.; Swan, Hilton B.; Maher, Damien T.; Jones, Graham B.; Schulz, Kai G.; Koveke, Edwin P.; Toda, Kei; Eyre, Bradley D. (Frontiers in Marine Science, 2022)
Earth’s Radiation Budget is partly dictated by the fragile and complex balance between biogenic volatile organic compounds (BVOCs) and greenhouse gases (GHGs), which have the potential to impose cooling or warming once emitted to the atmosphere. Whilst methane (CH4) is strictly associated with global warming due to its solar-radiation absorbing properties, dimethyl sulfide (DMS) is generally considered a cooling gas through the light scattering properties of its atmospheric oxidation products. However, DMS may also partially contribute to the Earth’s warming through a small portion of it being degraded to CH4 in the water column. Coral reefs emit both DMS and CH4 but they have not previously been simultaneously measured. Here, we report DMS and CH4 fluxes as well as aerosol particle counts at Heron Island, southern Great Barrier Reef, during the austral summer of 2016. Sea-to-air DMS and CH4 fluxes were on average 24.9 ± 1.81 and 1.36 ± 0.11 µmol m-2 d-1, whilst intermediate (< 0.5-2.5 um) and large (> 2.5 um) particle number concentrations averaged 5.51 x 106 ± 1.73 x 105 m-3 and 1.15 x 106 ± 4.63 x 104 m-3, respectively. Positive correlations were found between DMS emissions and the abundance of intermediate (R2 = 0.1669, p < 0.001, n = 93) and large (R2 = 0.0869, p = 0.004, n = 93) particles, suggesting that DMS sea-to-air emissions significantly contribute to the growth of existing particles to the measured size ranges at the Heron Island lagoon. Additionally, a strong positive correlation was found between DMS and CH4 fluxes (R2 = 0.7526, p < 0.00001, n = 93), suggesting that the emission of these volatile compounds from coral reefs is closely linked. The slope of the regression between DMS and CH4 suggests that CH4 emissions at the Heron Island lagoon represent 5% of that of DMS, which is consistent with the average fluxes reported in this study (i.e. 24.9 ± 1.81 µmol m-2 d-1 for DMS and 1.36 ± 0.11 for CH4). These findings provide new insights on the complexity of BVOC and GHG emissions in coral reef systems and their potential role in climate regulation.